ANALISIS TINGKAT KELAYAKAN BAHAN AJAR EKONOMI YANG DIGUNAKAN OLEH GURU DI SMA NEGERI 4 JEMBER - Yayuk Sri Rahayu Budiawati; Sri Kantun (JURNAL PENDIDIKAN EKONOMI: Jurnal Ilmiah Ilmu Pendidikan, Ilmu Ekonomi dan Ilmu Sosial, 2015)
One factor which influence the success of students’ learning is teaching material. So that’s why teachers have to be able in selecting the qualified teaching material because it will affect to the teachers’ quality especially the student’s quality. The aim of this study was to (1) to determine what materials are used by economics teacher at SMA Negeri 4 Jember and the reasons for the selection of the teaching material,, (2) to determine the feasibility of teaching materials used economics teacher at SMA Negeri 4 Jember. Data were collected in the form of primary data were analyzed using descriptive analysis and secondary data were analyzed using quantitative descriptive analysis. The results showed (1) the use of teaching materials such as textbooks on the grounds that electoral materials were used in accordance with the recent curriculum. The properness result of text book which is used is gained from thee xpert’s research sheet in term of content properness got 87%, presentation properness got 90%, language properness got 90,2%, and graphic properness got 87,5%. Therefore the average result is 88,7% with very appropriate criterion